Comparação entre métodos cromatográficos, empregando GC-ECD, GC-FPD e GC-MS, e espectrofotométrico para determinação de ditiocarbamatos em alface - Silva, Rosselei Caiél da (2005)
Brazil is the third largest market for pesticide sales in the world, with almost 400 active ingredients registered in the country, including five dithiocarbamates. This pesticide class consists of very important protective nonsystemic fungicides with broad-spectrum activity registered for the control of fungal deseases on a large variety of crops. Due to its low acute toxicity, combined with strong action, low-cost production and low environmental persistence, the total amount used of these compounds used is still increasing world-wide. Many methods to determine dithiocarbamates are based on acid hydrolysis in the presence of stannous chloride and analysis of the evolved CS2 by different techniques. In the present work, three chromatographic methods were validated for the quantification of dithiocarbamates residues in lettuce using Gas Chromatography with Electron Capture Detection (GC-ECD), Flame Photometric Detection (GC-FPD) and Mass Spectrometry (GC-MS), and these three methods were compared with a spectrophotometric method.The experimental conditions for the chromatographic analysis were: capillary column CP-Sil 8 CB (50 m x 0.32 mm i.d. x 1.2 μm film thickness); temperature program column oven: 45 oC (1 min) - 10 oC min-1 to 250 oC (0 min); flow-rate of the carrier gas (Helium) 2 mL min-1; volume of injection 4 μL, with split 1:10 for GC-ECD and GC-MS and 1:15 for GC-FPD; temperature of the detector was 300 oC for ECD and 250 °C for FPD. The transferline and trap were heated to 230 °C and the manifold to 120 °C. The spectrophotometric analysis was done in 435 nm, after complexation of the CS2 with diethanolamine and copper. In the validation study of the methods, the following parameters were assessed: detection limit (LOD), quantification limit (LOQ), precision (under repeatability and reproducibility conditions) and recovery. Method LODs in the sample were 0.01 mg CS2 kg-1 and 0.28 mg CS2 kg-1 and LOQs were 0.02 mg CS2 kg-1 and 0.4 mg CS2 kg-1 for chromatographic and spectrophotometric methods respectively. The calibration curves were linear with correlation coefficients r2> 0.99. Acceptable precision with RDS% between 2.8 and 15.9 was obtained. The recoveries ranged from 87.7 to 107.4%. The results obtained in the validation step allow us to conclude that the methods are quite appropriate to determine residues of dithiocarbamates in lettuce. However, the chromatographic methods have shown a lot of advantages such as to be more sensitive, simple and faster than the spectrophotometric method. Beside, the sample preparation can be done simultaneously for a great number of samples and in a simplified way.